PENYULUHAN MASYARAKAT TENTANG KOMERSIALISASI KOTORAN HEWAN SEBAGAI PUPUK KANDANG DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Bachrul Ulum (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The baiturrahman assembly is one of the Islamic study assemblies in Sukokerto village whose activities are scheduled and structured. The layout of the baiturrahman assembly is located in a strategic area to reach when compared to other assemblies. In addition, the problems faced by partners are quite specific compared to other assemblies in the Sukowono sub-district area, including the lack of knowledge of assembly participants regarding the commercialization of animal manure as drum fertilizer in Islamic views. There are still some of the assembly participants who doubt the customs carried out in their village for the transaction of animal manure, because most of the people in their area work as livestock keepers. The objectives of this Partnership Program include increasing the knowledge of the assembly participants regarding the commercialization of animal manure as kendang fertilizer in Islamic views, directing the assembly participants so that there are no more doubts about the transactions they have been doing since long ago. The method of implementing community service is carried out in several stages such as the observation stage, the interview stage, the documentation stage.